Anxiety to online learning: relationship with attitude, gender, environment, and mental health in university students - Castillo Riquelme, Victor (2021)
Introduction: The educational institution is one of the sectors that has suffered the most from the effects of the spread of Covid-19. Objective: This research aimed to characterize online learning anxiety through the eponymous dimension of the Online Learning Strategies Scale in a sample of university students (n = 192) and to examine its determinants. Methods: The study was quantitative, non-experimental and cross-sectional. Results: A regression model was used to explain 30% of the variability in online learning anxiety. Online learning anxiety was found to be negatively related to attitudes towards online classes, self-perceived mental health and quality of connectivity. Females reported higher anxiety than males. Conclusion: The article closes with recommendations for university policies and suggestions for further studies.